Feminist psychology and the new spirit of capitalism: Austrian feminist psychologists and new modes of work in the late 20th century - Ruck, Nora; Luckgei, Vera; Wanner, Lisa; Parzer, Elisabeth (Psychologie und Kritik, 2020)
This paper explores the ways in which feminist psychologists at an Austrian women’s counseling center both created and criticized their own working conditions during the mid 1980ies until the early 1990ies. Looking at both their concreted practices of counseling and of critique and at large scale social transformations in the sphere of work we analyze how these feminist psychologists produced psychological knowledge on the basis of which they criticized the social status quo. We also inquire what alternatives they envisioned and realized and how these alternatives rooted in larger scale transformations of society and how they fed back into society. We locate our analysis within a contextual history of psychology and focus on new modes of being and working that activists of the second wave of feminism paved the way for mostly in the form of women’s collectives and feminist project work, in order to situate the psychological knowledge produced by feminist psychologists and psychosocial practitioners working at a counseling center for women. In a next step, we rely on the concept of the new spirit of capitalism and the role of critique in societal transformation in order to analyze how feminist counseling centers were not only rooted in their social, cultural, and economic contexts, but also fed back into these contexts by co-creating new modes of work while at the same time critically reflecting upon their own working conditions. We thus describe the relationship between feminist psychology and its social context as circular: While women’s counseling centers were both affected and brought forth by their social context, their efforts and activities changed not only the psychosocial support system, but also the working conditions in this field.